If it's not what You are looking for type in the equation solver your own equation and let us solve it.
17=-3(23-m)+2(m-2)
We move all terms to the left:
17-(-3(23-m)+2(m-2))=0
We add all the numbers together, and all the variables
-(-3(-1m+23)+2(m-2))+17=0
We calculate terms in parentheses: -(-3(-1m+23)+2(m-2)), so:We get rid of parentheses
-3(-1m+23)+2(m-2)
We multiply parentheses
3m+2m-69-4
We add all the numbers together, and all the variables
5m-73
Back to the equation:
-(5m-73)
-5m+73+17=0
We add all the numbers together, and all the variables
-5m+90=0
We move all terms containing m to the left, all other terms to the right
-5m=-90
m=-90/-5
m=+18
| -2+m/9=-3 | | 6i-3=-18+i | | p+7/3=7 | | -8x-18=-274 | | 47=31-4(x-2) | | p+6/3=3 | | 16x+19=595 | | x-5/6=-1/6 | | n=9/10=-4 | | p–5=-2 | | 22=2h+10 | | -4.5+3=2-8.5x | | B.2/3b-1/3b=4/3 | | 39=26-b | | 7l-4=2l+16 | | -66=-3(m+5) | | 15=-5t^2+20t+1 | | 4(-x+2)=x-5+3 | | 5b+5=14+2b | | -3/7h=42 | | 5(2t-3)-7.5t=0.5(12-0) | | x=8,2x-10 | | -9(-6+b)=135 | | 30-n=59 | | -10(n+1)=60 | | 296-3x=444-5x | | -8=-29-n | | 14=g+5 | | 24=g+5 | | 21/27=x/8 | | -14=1-x | | 2=3+x/6 |